140 UTEROPLACENTAL INSUFFICIENCY AFFECTS HIPPOCAMPAL INSULIN-LIKE GROWTH FACTOR 1 MESSENGER RIBONUCLEIC ACID LEVELS IN JUVENILE RATS. Issue 1 (1st January 2007) - Schober, M.; Ke, X.; Yu, X.; Callaway, C.; Men, P.; McKnight, R.; Lane, R.
Abstract : Background: Intrauterine growth retardation (IUGR) predisposes affected human and rat newborns toward persistent hippocampal dysfunction. This often occurs in association with low circulating insulin-like growth factor 1 (IGF-1) levels. Both circulating IGF-1 and locally produced IGF-1 are required for normal hippocampal development and adult cognitive function. However, the effects of IUGR upon hippocampal IGF-1 expression are not known. Objective: We hypothesized that uteroplacental insufficiency (UPI) and subsequent IUGR would decrease postnatal hippocampal IGF-1 mRNA levels. IGF-1 expression involves multiple promoters (P1, P2) and multiple exon variants (IGF-1A, IGF-1B). Each exon variant produces a different E peptide. Design/Methods: We used a well-characterized rat model of UPI-induced IUGR: briefly, bilateral uterine artery ligation was performed on day 19 of gestation (term-21.5 d). Litters were culled to six after birth, and brain was harvested and dissected at day 21 of postnatal life (D21). In this model, we have shown that IUGR animals perform poorly on tests of hippocampal function at adulthood. They also have abnormal anatomic and functional hippocampal markers, as well as low serum IGF-1 levels. IGF-1 mRNA variants and total IGF-1 mRNA were quantified by real-time RT-PCR ( n = 6-8 litters). Results: Data are expressed as % of control. IUGR significantly decreased D21 hippocampal P1 IGF-1 mRNA levels in both male and female rats to 87% of control values ( p = .02). As expected, male rats were more severely affected than the female rats. Expression of the IGF-1B mRNA was also significantly decreased in D21 IUGR hippocampal samples to 77.3% of control values ( p = .01). Surprisingly, the IGF-1B mRNA levels were more severely in the female IUGR rats versus the male rats. Conclusion: Despite low serum levels of IGF-1, hippocampal IGF-1 expression is not up-regulated in P21 IUGR rats. In addition, P1, an IGF-1 mRNA that predominates in the brain and is believed to be the paracrine form of IGF-1, is decreased by IUGR. Finally, IGF-1B, an mRNA variant thought to encode the EB peptide, a peptide that may be important in neuronal differentiation, is also decreased by IUGR. These findings are interesting in the up-regulation of cerebral IGF-1 normally occurs in response to acute hypoxia-ischemia. We speculate that the failure of the IUGR hippocampus to increase IGF-1 mRNA levels contributes to the neurocognitive dysfunction observed in both the IUGR human and rat. ( CHRC )